Donor- and isolation-related predictive factors of in vitro secretory function of cultured human islets - Buemi, Antoine; Mourad, Nizar I.; Ambroise, Jérôme; Hoton, Delphine; Devresse, Arnaud; Darius, Tom; Kanaan, Nada; Gianello, Pierre; Mourad, Michel (Frontiers in Endocrinology, 2024)
Background and aims Human islet preparations designated for research exhibit diverse insulin-secretory profiles. This study aims to assess the impact of donor- and isolation-related factors on in vitro islet secretory function. Methods A retrospective analysis of 46 isolations from 23 pancreata discarded for clinical transplantation was conducted. In vitro islet secretory function tests were performed on Day 1 and Day 7 of culture. Linear mixed-effects models (LMMs) were employed to investigate the relationships between various predictors characterizing the patient and donor characteristics as well as the isolation effectiveness and two functional outcomes including the islet stimulation index (SI) and area under the insulin curve (AUC). Fixed effects were introduced to represent the main effects of each predictor, and backward elimination was utilized to select the most significant fixed effects for the final model. Interaction effects between the timepoint (Day 7 vs. Day 1) and the predictors were also evaluated to assess whether predictors were associated with the temporal evolution of SI and AUC. Fold-change (Fc) values associated with each predictor were obtained by exponentiating the corresponding coefficients of the models, which were built on log-transformed outcomes. Results Analysis using LMMs revealed that donor body mass index (BMI) (Fc = 0.961, 95% CI = 0.927–0.996, p = 0.05), donor gender (female vs. male, Fc = 0.702, 95% CI = 0.524–0.942, p = 0.04), and donor hypertension (Fc = 0.623, 95% CI = 0.466–0.832, p= <0.01) were significantly and independently associated with SI. Moreover, donor gender (Fc = 0.512, 95% CI = 0.302–0.864, p = 0.02), donor cause of death (cerebrovascular accident vs. cardiac arrest, Fc = 2.129, 95% CI = 0.915–4.946, p = 0.09; trauma vs. cardiac arrest, Fc = 2.129, 95% CI = 1.112–7.106, p = 0.04), pancreas weight (Fc = 1.01, 95% CI = 1.001–1.019, p = 0.03), and islet equivalent (IEQ)/mg (Fc = 1.277, 95% CI = 1.088–1.510, p ≤ 0.01) were significantly and independently associated with AUC. There was no predictor significantly associated with the temporal evolution between Day 1 and Day 7 for both SI and AUC outcomes. Conclusion This study identified donor- and isolation-related factors influencing in vitro islet secretory function. Further investigations are essential to validate the applicability of these results in clinical practice.